2014
DOI: 10.1159/000365167
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenese und pleiotrope Behandlungsansätze bei diabetischen Folgeerkrankungen - Übersicht über Wirkmechanismen von Padma® 28

Abstract: Diabetes mellitus Typ 2 hat aufgrund seiner hohen Prävalenz, seines chronischen Verlaufs und seiner Folgeerkrankungen eine grosse medizinische, aber auch eine sozioökonomische Bedeutung. Es handelt sich um eine komplexe Erkrankung mit einer Vielzahl an pathogenen Faktoren, wobei neben der metabolischen Störung vor allem auch chronisch entzündliche Prozesse beteiligt sind. Oxidativer Stress und die Bildung von Advanced Glycation Endproducts (AGE) spielen eine zentrale Rolle bei der Entstehung und dem Fortschrei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…a protective effect on blood vessels (both in micro- and macrovascular areas), efficacy in peripheral atherosclerosis, and immunostimulatory and anti-inflammatory mechanisms of action. Padma formulations have also been shown to be able to scavenge free radicals and reduce the oxidation of lipids [ 17 , 19 , 26 , 47 ]. In our earlier study [ 17 ] we demonstrated their strong ability to inhibit T-AGE and T-AOPP formation (by 56 and 66 %, respectively, for oxidation and glycation).…”
Section: Discussionmentioning
confidence: 99%
“…a protective effect on blood vessels (both in micro- and macrovascular areas), efficacy in peripheral atherosclerosis, and immunostimulatory and anti-inflammatory mechanisms of action. Padma formulations have also been shown to be able to scavenge free radicals and reduce the oxidation of lipids [ 17 , 19 , 26 , 47 ]. In our earlier study [ 17 ] we demonstrated their strong ability to inhibit T-AGE and T-AOPP formation (by 56 and 66 %, respectively, for oxidation and glycation).…”
Section: Discussionmentioning
confidence: 99%